2007
DOI: 10.1063/1.2717576
|View full text |Cite
|
Sign up to set email alerts
|

Protein destruction by a helium atmospheric pressure glow discharge: Capability and mechanisms

Abstract: Citation: DENG X.T., SHI, J.J. and KONG, M.G., 2007. Protein destruction by a helium atmospheric pressure glow discharge: capability and mechanisms.Journal of Applied Physics, 101 (7), article 074701, pp.1-9.Additional Information:• Biological sterilization represents one of the most exciting applications of atmospheric pressure glow discharges ͑APGD͒. Despite the fact that surgical instruments are contaminated by both microorganisms and proteinaceous matters, sterilization effects of APGD have so far been stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(117 citation statements)
references
References 24 publications
3
111
1
2
Order By: Relevance
“…Vleugels and co-workers (2005) Survival of food-borne pathogens has been detected at a level of 10 5 CFU/cm 2 on stainless steel surfaces in a study by Kusumaningrum et al (2003). Deng et al (2009) showed that cold gas plasmas have the potential to denaturize proteins attached to stainless steel. Gas plasmas could also be used to remove allergens from the surface of ).…”
Section: Control Of Biofilms and Decontamination Of Processing Surfacesmentioning
confidence: 99%
“…Vleugels and co-workers (2005) Survival of food-borne pathogens has been detected at a level of 10 5 CFU/cm 2 on stainless steel surfaces in a study by Kusumaningrum et al (2003). Deng et al (2009) showed that cold gas plasmas have the potential to denaturize proteins attached to stainless steel. Gas plasmas could also be used to remove allergens from the surface of ).…”
Section: Control Of Biofilms and Decontamination Of Processing Surfacesmentioning
confidence: 99%
“…Such low-temperature plasmas are commonly known as cold atmospheric plasmas (CAPs) and have been shown to be capable of effectively inactivating bacteria, fungi and virus, inducing apoptosis in cancer cells, and stimulating proliferation of mammalian cells, all in a dose-dependent fashion [52] [53]. Today, CAPs are increasingly used in an impressive array of healthcare applications such as blood coagulation [58], skin disinfection [58] [59] and wound disinfection [60], wound healing [61], sterilisation of surgical instruments and medical devices [62], cancer therapy [63], and food decontamination [64]- [66]. Their potentials for healthcare are profound and their clinical successes so far are exceptionally encouraging [67][68], thus fuelling a rapid expansion of research activities in an emerging but now highly visible field known as plasma medicine.…”
Section: Interaction Of Plasmas With Cellsmentioning
confidence: 99%
“…As a result HeþO 2 plasmas are typically operated with reduced amount of oxygen and maximum process efficacy is often encountered at oxygen concentrations below 1%. 44,45 In the last decades, global models have been used to study low-pressure electronegative plasmas [46][47][48][49] and in recent years these models have been extended to the study electronegative atmospheric-pressure discharges. [15][16][17][18] In these models it is customary to assume that the input power is mainly coupled to the electrons 50 with various approximations regarding the power coupled to ions in the sheath.…”
Section: -mentioning
confidence: 99%
“…As a result, atmospheric pressure plasmas are being explored for a large variety of applications including plasma medicine, [1][2][3] air purification, 4,5 sterilization, 6,7 surface modification, 8,9 and water treatment. 10,11 Many of these applications rely on the production of reactive oxygen species (ROS), which can be obtained readily in atmospheric-pressure cold plasmas in gases containing admixtures of O 2 and=or H 2 O.…”
Section: Introductionmentioning
confidence: 99%